PENGARUH KETERLIBATAN PELANGGAN, KUALITAS LAYANAN, CITRA MEREK DAN PENGALAMAN MEREK TERHADAP KEPUASAN PELANGGAN PADA PENGGUNA TRANSPORTASI ONLINE DI DKI JAKARTA - Dwi Atmoko, Yudi; Riorini, Sri Vandayuli; Hidasanita, Helzya; Tahira, Nina (Institut Shanti Bhuana, Program Studi Kewirausahaan, 2024)
The research aims to find out how influential customer involvement, the quality of service, the brand image and brand experience of customer satisfaction on online transport users. This study is aimed at grab, one of southeast Asia's transportation services. The data collection on this research USES field research by spreading